Qualidade de vida e autoestima em mulheres mastectomizadas por neoplasia mamária - Manfredini, Rinede Luís (2019)
The objective was to evaluate the influence of modified radical mastectomy surgery on the treatment of breast cancer in the quality of life and self-esteem of women who did not perform breast reconstruction. The research problem was to understand the influence of modified radical mastectomy on the quality of life and self-esteem of women with breast cancer. The study is cohort, descriptive and analytical. The study population consisted of 62 women who underwent radical modified mammary mastectomy surgery in the municipality of Erechim / RS, from January 2006 to January 2016. The identification data were obtained in the electronic medical record of the Emergency Care Unit High Complexity of this city. The data were obtained after express authorization from the management of the institution. All the women who underwent mastectomy by the Unified Health System answered the instruments and the data collection questionnaire. The documents are sent by post. To analyze the effects, form the WHOQOL-bref quality of life tests and Rosenberg's Self-esteem Scale, together with the questionnaire prepared for socioeconomic characterization of the studied population. The data is analyzed using the R language 3.3.2. To analyze the effects, the following Chi-square and Fisher's exact tests were used. The significance level set for rejection of H0 was s = 0.05. The main contribution of this study was the description of the effects of modified radical mastectomy for the treatment of breast neoplasia, quality of life and self-esteem of women who did not perform breast reconstruction.